COLONIZATION AND MORPHOLOGICAL CHANGES OF A SEDGE RESTRICTING REGENERATION AFTER WIND DAMAGE IN A NATURAL FOREST - Teruo Arase; Tetsuo Okano; Tetsuoh Shirota (GEOMATE Journal, 2016)
Many old trees were blown down by typhoons in 1959 and 1961 in a natural coniferous forest deep in the mountains of Kiso District, Central Japan, and dense dwarf bamboo subsequently delayed the growth of tree seedlings. Forest engineers have tried to suppress dwarf bamboo to promote the regeneration of arboreal vegetation. However, after suppression of dwarf bamboo, an unknown grass unexpectedly colonized the area and replaced them. Afterward, almost no tree seedlings could be observed in the newly formed community, which seemed to worsen the extent of regeneration. It has been identified that the grass as Carex oxyandra, a native sedge species indigenous to Kiso District. Commonly, Carex oxyandra grows as short as about 10 cm like lawn grass, but it seems to have exceedingly enlarged the size in the community. Thus, investigation on the morphological variation of this sedge in Miure Experimental Forest within the Kiso National Forest was carried out. Leaf blade length, basal tiller length, and number of leaves per tiller were measured in upper and lower stands on three slopes in 2009. Results revealed that leaf blade length and basal tiller length in lower stands were approximately twice as large as those in upper stands on each slope, whereas the number of leaves per tiller was almost the same (8.8-9.4 leaves). Consequently, tussocks of this sedge became large in lower stands on a slope, which made the community overcrowded and damp, restricting tree regeneration.